2014
DOI: 10.1073/pnas.1411837111
|View full text |Cite|
|
Sign up to set email alerts
|

Selective filtering defect at the axon initial segment in Alzheimer’s disease mouse models

Abstract: Axon pathology has been widely reported in Alzheimer’s disease (AD) patients and AD mouse models. Herein we report that increased miR-342–5p down-regulates the expression of ankyrin G (AnkG), a protein known to play a critical role in establishing selective filtering machinery at the axon initial segment (AIS). Diminished AnkG expression leads to defective AIS filtering in cultured hippocampal neurons from AD mouse models, as monitored by selective exclusion of large macromolecules from the axons. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 48 publications
3
59
0
Order By: Relevance
“…Finally, we showed that ankG and sodium channels are dispersed along the axon on exposure to Ab. Consistently, a recent report showed defective filtering at the axon initial segment in cultured neurons from an AD mouse model 66 . In conclusion, as summarized in the model shown in Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Finally, we showed that ankG and sodium channels are dispersed along the axon on exposure to Ab. Consistently, a recent report showed defective filtering at the axon initial segment in cultured neurons from an AD mouse model 66 . In conclusion, as summarized in the model shown in Fig.…”
Section: Discussionsupporting
confidence: 81%
“…AnkG gene variants and mutations have been consistently associated with in several neuropsychiatric disorders, including bipolar disorders and schizophrenia (Iqbal et al, 2013;Leussis et al, 2012). Furthermore, affected axonal transport is a key factor in most neurodegenerative diseases, and the gatekeeper function of the AIS could be implicated (Sun et al, 2014). Our structural work will hopefully open the way to a better understanding of the AIS crucial functions, in physiological as well as pathological contexts.…”
Section: Role Of Ankg In Regulating Protein Transport Trough the Aismentioning
confidence: 85%
“…Axonal pathology in the APP/PS1 mouse model of Alzheimer’s is due in part to a decrease in AnkG and thus impairment of the AIS, which can be rescued by forced expression of AnkG. 69 Further, CDK5 activation is altered in a number of neurodegenerative diseases including Alzheimer’s 70 and ALS 71 ; dysregulated CDK5 may adversely impact polarized sorting in neurons as well as affecting transport along the axon, leading to further enhancement of cellular stress.…”
Section: Discussionmentioning
confidence: 99%